BOOK REVIEW: Alin Fumurescu, “Compromisul: o istorie politică şi filozofică”, Bucureşti: Humanitas, 2019 - GLĂVAN, Bianca (Studia Universitatis Babeș-Bolyai Historia, 2019)
Alin Fumurescu, Assistant Professor at the Department of Political Science at University of Houston, expressed his research interests in the history of ideas, medieval and modern political theory, political and self-reprezentation, American political thought. He was the recipient of the American Political Science Association Leo Strauss Award for the best doctoral dissertation in political philosophy for 2013. The political scientist’s connections with Romania remained strong, the proof is his collaboration with different Romanian newspapers, but also the launch of his book in Romanian translation with a special preface. The book we are focusing on is a valuable research regarding conceptual history, history of ideas, philosophy and political theory. Fumurescu wrote the first conceptual history of the notion of compromise, although he prefers the term genealogy instead of history because, following Michel Foucault, he considers that genealogy suggests a more unpredictable development. The author pays attention to the meaning continuities and changes concerning the concept of compromise, trying to place them in the appropriate historical context. Such an approach is supported by the fact that people live with meanings, and meanings are transmitted through words. And, depending on howwe use certain words, it changes the way we relate to the world. Even more, we can ask ourselves whether or not reality can be constructed through words. Some thinkers believe there are make-up beliefs, but that does not imply the idea of falsehood. For example, Benedict Anderson considers that the nation is an imagined but not imaginary concept, which means that it becomes a reality.